Synthesis, biological activity of a new long-chain di-Schiff base ligand and Ru(II) complex in solvent-free conditions - Demirhan, Nebahat; Peksel, Aysegul; Elmali, Fikriye Tuncel; Eren, Murfe (IOS PRESS, 2017)
A new Long-chain, di-Schiff base ligand (N2O2 donor, L) has been synthesized by the reaction of dodecylamine with, 1,5-bis(2'-formylphenyl)-1,5-dioxapentane in molar, 2: 1 ratio (yielded 82%) and its Ru(II) complex have been prepared (yielded 78%) in solvent-free conditions. The newly synthesized compounds have been verified by ATR-IR, UV-vis., mass (LC-MS and MALDI-TOF) andNMR(H-1, C-13) spectra, elemental and thermal analysis. TheDNAbinding studies of the ligand and complex were examined by absorption method. The results indicated that the ligand and Ru(II) complex could interact with calf thymus DNA (CT-DNA) through electrostatic or/and groove binding (minor/major). The apparent binding constant values (Kb) of the ligand and Ru(II) complex at room temperature were calculated to be 5.9x10(5) M-1 and 7.9x10(5) M-1, respectively. Antioxidant study of the ligand and complex showed significant antioxidant activity against lipid peroxidation. The ligand and complex also have moderate radical scavenging properties.
Keywords: Di-Schiff base; solvent-free reactions; antioxidative activities; DNA binding; CRYSTAL-STRUCTURE; DNA-BINDING; ANTIOXIDANT; CLEAVAGE; Chemistry